Overdose Awareness and Reversal Trainings at Philadelphia Public Libraries. Issue 2 (February 2021) - Lowenstein, Margaret; Feuerstein-Simon, Rachel; Dupuis, Roxanne; Herens, Allison; Hom, Jeffrey; Sharma, Meghana; Sheni, Risha; Encarnacion, Lonard; Flaherty, Carina; Cueller, Maria; Cannuscio, Carolyn
Purpose: To evaluate an overdose response training program in public libraries. Design: Mixed methods evaluation including pre- and post-intervention questionnaires and debriefing interviews. Setting: Ten Philadelphia public libraries. Sample: Overdose response training participants (library staff and community members). Intervention: Public, hour-long overdose response trainings run by the Philadelphia Department of Public Health, the Free Library of Philadelphia, and the University of Pennsylvania between March and December 2018. Measures: Questionnaires assessed motivation for attending trainings, overdose response readiness, and intention to acquire and carry naloxone. Debriefing interviews elicited training feedback. Analysis: We assessed changes in overdose response readiness and intention to carry naloxone and performed thematic analysis on interview data. Results: At 29 trainings, 254 people attended, of whom 203 (80%) completed questionnaires and 23 were interviewed. 30% of participants had witnessed an overdose, but only 3% carried naloxone at baseline. Following training, overdose response readiness and intention to acquire/carry naloxone improved significantly ( P < .01). Interviewees nonetheless noted that they experienced barriers to naloxone acquisition, including cost, stigma, and concern regarding future insurability. Trainings subsequently included naloxone distribution. Interviewees reported that public libraries were welcoming, nonstigmatizing venues. Conclusion: In Philadelphia, library-based overdose response trainings were well-attended and reached a population with prior overdose encounters. Similar trainings could be deployed as a scalable overdose prevention strategy in the nation's 16 568 public libraries.